The Influence of Occupational Safety Training on Compliance With The Use of PPE in Health Facilities - Hardianty, Hardianty; Sari, Siti Nurmanis; Deviyanti, Andi Yepita (Oshada, 2025)
This study aims to analyze the effect of occupational safety training on compliance with the use of Personal Protective Equipment (PPE) in healthcare facilities. The background of the study is based on the high risk of exposure to occupational hazards faced by healthcare workers and the low consistency in the correct use of PPE. This study used a quantitative method with a survey approach and simple linear regression analysis of 100 healthcare worker respondents consisting of nurses, midwives, and laboratory personnel. The results showed that occupational safety training had a positive and significant effect on compliance with PPE use with a regression coefficient value of 0.684, a t-test of 9.247, and a significance level of 0.000. The coefficient of determination (R²) value of 0.468 indicates that the training was able to explain 46.8% of the variation in healthcare worker compliance. These findings indicate that structured, interactive, and simulation-based training is more effective in increasing awareness and compliance with safety procedures. Organizational support and ongoing supervision also strengthen the training outcomes so that safe behavior can be maintained in the long term. This study confirms that occupational safety training is a strategic instrument for strengthening OSH culture and creating a safe and productive work environment in the healthcare sector.